Are we no different from psychopaths? - Wong, Pearline Young Yin (Nanyang Technological University, 2021)
When we first think of moral motivation, we would naturally think that every person possesses it. We would think of instances where we did something good or instances when we held back from a vice. However, it is on closer study of the world and the cruelty that it contains which makes us question the existence of moral motivation. In a world where individuals have committed moral wrongs contributing to existing cruelties, does it set them apart from psychopathic individuals who commit immoral acts without qualms? C. Daniel Batson contends that moral motivation exists but rarely, while Joshua May contends that moral motivation is prevalent. Through studying the debate between Batson and May on moral motivation, the case study of psychopathy and examples of moral and seemingly immoral acts committed by non-psychopaths, this paper aims to show that moral motivation is not only existing but prevalent.